Travel-associated human trichinellosis in Portugal. (2021) - Vale, Francisco; Azevedo, Telma; Lima, Maria; Oliveira, Inês; Parreira, Mário; Anes, Margarida; Bajanca, Rui; Gargaté, Maria João; Poças, José
Highlights: This is the first case of human trichinellosis reported in Portugal in the last 30 years. Trichinella spp. infection is a re-emerging foodborne parasitic zoonotic disease. Trichinellosis must be considered in the differential diagnosis of hypereosinophilia. Abstract: Trichinellosis is an emerging or re-emerging foodborne parasitic zoonotic disease caused by nematodes of the genus Trichinella . It represents a global food safety problem and a public health hazard. This case report aims to describe the first case of human trichinellosis in Portugal since the creation of the European Union surveillance system. Infection by Trichinella spp. is a rare cause of hypereosinophilia and hospital admission, but it can cause high morbidity. Clinical detailed history is crucial to obtain a correct diagnosis.